Spatial disparity of skill premium in China: The role of financial intermediation development - Tat-kei Lai; Luhang Wang (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
In China, the relative wages of high-skilled and low-skilled workers display huge variation across different regions. We examine whether financial intermediation development can explain such variation. Conceptually, better-developed financial intermediation helps financially-constrained firms raise new capital, which is usually skilledbiased, resulting in an increased demand for skilled labor and skill premium. Using a cross-section of workers from the 1% Population Survey of 2005, we find consistent evidence; besides, the relationship is stronger among workers in industries with higher capital-skill complementarity and in non-state-owned enterprises. Overall, our results suggest that the financial market plays a role in explaining skill premium in China.
urn:nbn:fi:bof-202207141333
Keywords: J24; J31; O11; 330; Financial intermediation; Misallocation; Skill premium; China